2009
DOI: 10.1111/j.1741-3737.2009.00636.x
|View full text |Cite
|
Sign up to set email alerts
|

Unpacking Racial Socialization: Considering Female African American Primary Caregivers' Racial Identity

Abstract: The relationship between female African American primary caregivers’ racial identity and their racial socialization emphases was examined. Three components of racial identity were evaluated: (1) the importance of race to the self-concept (centrality); (2) affective feelings towards group membership (private regard); and, (3) perceptions of how group members are perceived by nonmembers (public regard). Latent class cluster analysis was used to identify racial identity profiles, or dominant combinations of racia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 38 publications
0
22
1
Order By: Relevance
“…Racial identity has been conceptualized as individuals' belonging to their racial group as well as their beliefs regarding their racial group membership (Cross, ; Phinney, ; Sellers et al, ). Previous research has indicated that parents' racial identity attitudes may shape the frequency and content of racial socialization messages (Hughes & Johnson, ; Scottham & Smalls, ). Studies examining the relationship between racial identity and racial socialization have found that parents with more salient racial identities are more likely to communicate race‐related messages to their children (Hughes, ; Thomas & Speight, ).…”
Section: Traditional Approaches To Racial Socialization Processes Amomentioning
confidence: 99%
“…Racial identity has been conceptualized as individuals' belonging to their racial group as well as their beliefs regarding their racial group membership (Cross, ; Phinney, ; Sellers et al, ). Previous research has indicated that parents' racial identity attitudes may shape the frequency and content of racial socialization messages (Hughes & Johnson, ; Scottham & Smalls, ). Studies examining the relationship between racial identity and racial socialization have found that parents with more salient racial identities are more likely to communicate race‐related messages to their children (Hughes, ; Thomas & Speight, ).…”
Section: Traditional Approaches To Racial Socialization Processes Amomentioning
confidence: 99%
“…Within this sample, the fourth cluster (low affiliation, which is characterized by low centrality, low private regard, and moderate public regard scores) parallels a pattern identified among African American adults (Scottham & Smalls, 2009). The fourth cluster identified among adolescents was characterized by low centrality, high private regard, and low public regard (labeled low connectedness=high affinity).…”
Section: Discussionmentioning
confidence: 65%
“…In a separate study also involving cluster analysis, Scottham and Smalls (2009) found support for a four-cluster solution, replicating the buffering= defensive and idealized dimensions among a sample of African American adults. Two additional profiles were identified: a moderate profile, which paralleled the alienated group reported by Chavous and colleagues (2003) but with low centrality and regard scores hovering more closely around the standardized mean; and a low affiliation profile, characterized by low centrality, low private regard, and high public regard.…”
Section: Please Scroll Down For Articlementioning
confidence: 63%
See 1 more Smart Citation
“…1 The majority of studies that included ethnicity do not address the fundamentally different ideologies inherent in African American, Anglo, and Latino fathers' construction of fathering and childrearing practices, opting instead to examine the role that discrimination and a legacy of poverty have on ethnic children's limited opportunities for economic success (Farley 1980;Horton and Thomas 1995;Lerman and Ooms 1993;Massey and Denton 1993;Zimmerman et al 1995). Recent research is examining the importance of ethnicity in parenting processes and child socialization (Benner and Kim 2009;Scottham and Smalls 2009).…”
mentioning
confidence: 96%